2018
DOI: 10.1055/s-0038-1636948
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Mesenchymal Stem Cells of Bursal Tissue after Rotator Cuff Repair in Rats

Abstract: Purpose  The purpose of this study is to verify migration of mesenchymal stem cells of bursal tissue into the healing site after rotator cuff repair in rats. Methods  Fischer rats and green fluorescent protein (GFP)-transgenic rats were used. Bursal tissue from GFP rats was isolated and transplanted into tendon repair sites in Fischer rats. We examined the histology of the rotator cuff and the proportion of GFP-positive cells in the repaired rotator cuff 1, 3, and 6 weeks after surgery. Results  Cell migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In studies regarding rotator cuff repair after injury, some researchers have suggested that healing always seems to begin on the lateral side of the bursa. 12,22,26,30 Intriguingly, histologic cartilage staining reportedly shows that the generation of new cartilage in the tendon-bone transition area is always faster on the lateral side of the tendon. 31,32 Thus, the lateral side is the main and more reliable source of rotator cuff healing, and the healing speed is significantly faster than that of the medial side, especially at the tendon-bone junction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies regarding rotator cuff repair after injury, some researchers have suggested that healing always seems to begin on the lateral side of the bursa. 12,22,26,30 Intriguingly, histologic cartilage staining reportedly shows that the generation of new cartilage in the tendon-bone transition area is always faster on the lateral side of the tendon. 31,32 Thus, the lateral side is the main and more reliable source of rotator cuff healing, and the healing speed is significantly faster than that of the medial side, especially at the tendon-bone junction.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have shown that the lateral tendon is promising and important in healing promotion in the shoulder joint. 12,18,22,26 However, no relevant study has explored lateralized microfracture in an animal model.…”
mentioning
confidence: 99%
“…46,47 The subacromial bursa is a good candidate source of MSCs in rotator cuff tears. 48,49 In addition, MSCs were found in bursal tissue infiltrate in repaired rotator cuff tendons after rotator cuff repair in an animal model. 50 Rotator cuff MSCs also express lineage-specific genes, such as Runt-related transcription factor 2 ( Runx2 ) and osteocalcin in osteogenic induction, peroxisome proliferator-activated receptor gamma ( PPARγ ) and lipoprotein lipase ( LPL ) in adipogenic differentiation, and aggrecan and collagen type II α1 ( ColIIα1 ) in chondrogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…None of the small animal studies included in this review specifically addressed MSC homing to tendon lesions. However, when bursal tissue was implanted in rotator cuff tendon lesions in a rat model, the green fluorescent protein-labeled mesenchymal stem cells from this tissue infiltrated the healing tendons [159], demonstrating the presence of homing signals. Accordingly, ASC infiltration into the tendons was also evident when cell sheets were used as delivery vehicle in a canine model [126].…”
Section: In Vivo Evidencementioning
confidence: 99%